The Urgency of Sugar Sweetened Beverages Excise Policy: A Literature Study for Implementation in Indonesia - Hambali, Mohamad Luhur (UI Scholars Hub, 2022)
Diabetes diseases should become an alert for all people around the world, including Indonesia. Being one of the ten diseases that are classified as dangerous diseases, diabetes is estimated to infect 700 million people by 2045. Strategic steps must be taken by the Indonesian government, one of them is through the implementation of fiscal policy on the collection of Sugar Sweetened Beverages (SSB) Excise. Using secondary sources data through literature review by looking for information about countries that have implemented the SSB Excise, this paper goals are to analyze the urgency of implementing a SSB Excise that can be applied by the Indonesian government, by reflecting on the implementation of policies that have been implemented in other countries around the world. This paper is limited to the number of extensive and in-depth related research, and still not describe yet using a full detail research method about the evidence which related to the urgency of this excise policy, so it would be beneficial for other researcher, especially in Indonesia who would make it depth. The result of this paper is that the SSB Excise policy is appropriate and should be implemented in Indonesia, in the form of implementing the Excise Tax in the sugar sweetened beverage industry, which can imitate the excise policies of the UK & Thailand. So that the results of this SSB Excise revenue can be earmarked for the benefit of overcoming health costs caused by diabetes, as well as improving health-based public facilities.